Fluoridation referendum in La Crosse, Wisconsin: contributing factors to success. - Jones, R B (1989)
Residents of La Crosse, Wisconsin approved a public referendum in favor of water fluoridation on April 5, 1988. The vote, 57 percent supportive, culminated a two-year community effort. Three public referenda had been defeated in the past. Contributing to the success of this recent campaign were: broad-based community support led by a 34-member Citizens for Better Dental Health in La Crosse Committee; American Dental Association/Wisconsin Division of Health/US Public Health Service consultation and support; knowledgeable and supportive press coverage; the timing of the ballot to coincide with the Wisconsin Presidential Primary; and local chiropractic support to offset chiropractic anti-fluoridation leadership. La Crosse, population 50,000, was the largest fluoride-deficient community in a nine-state upper Midwest area.